Distorsiones cognitivas en pacientes consumidores de sustancias psicoactivas en función de sus características sociodemográficas, en una IPS. (2021)
The present research aims to describe the type of cognitive distortions that take place in 17 patients made up of 82% men and 18% women from the IPS “Nuevo Amazonas” in Leticia, starting from their sociodemographic characteristics. All the participants reported a problematic consumption of psychoactive substances and were in-patients. This study was carried out as a descriptive, quasi-experimental model and the results were obtained from the correlation of the application of a sociodemographic survey and the automatic thought inventory instrument of Ruiz and Lujan (1991). It was showed that the population under study presented levels of cognitive distortion depending on the sociodemographic characteristics, showing that heteronomy and the external locus of control are part of the cognitive and ideational repertoire of patients who consume psychoactive substances, which leads them to avoid introspection and self-criticism